Investments for effective functionality of health systems towards Universal Health Coverage in Africa: A scoping review. - Humphrey Cyprian Karamagi; Ali Ben Charif; Solyana Ngusbrhan Kidane; Tewelde Yohanes; David Kariuki; Maritza Titus; Charles Batungwanayo; Aminata Binetou-Wahebine Seydi; Araia Berhane; Jacinta Nzinga; David Njuguna; Hillary Kipchumba Kipruto; et al. (PLOS Global Public Health)
The health challenges in Africa underscore the importance of effectively investing in health systems. Unfortunately, there is no information on systems investments adequate for an effective functional health system. We aimed to address this by conducting a scoping review of existing evidence following the Joanna Briggs Institute Manual for Evidence Synthesis and preregistered with the Open Science Framework (https://osf.io/bvg4z). We included any empirical research describing interventions that contributed to the functionality of health systems in Africa or any low-income or lower-middle-income regions. We searched Web of Science, MEDLINE, Embase, PsycINFO, Cochrane Library, CINAHL, and ERIC from their inception, and hand-searched other relevant sources. We summarized data using a narrative approach involving thematic syntheses and descriptive statistics. We identified 554 unique reports describing 575 interventions, of which 495 reported evidence of effectiveness. Most interventions were undertaken in Africa (80.9%), covered multiple elements of health systems (median: 3), and focused on service delivery (77.4%) and health workforce (65.6%). Effective interventions contributed to improving single (35.6%) or multiple (64.4%) capacities of health systems: access to essential services (75.6%), quality of care (70.5%), demand for essential services (38.6%), or health systems resilience (13.5%). For example, telemedicine models which covered software (technologies) and hardware (health workers) elements were used as a strategy to address issues of access to essential services. We inventoried these effective interventions for improving health systems functionality in Africa. Further analyses could deepen understanding of how such interventions differ in their incorporation of evidence for potential scale across African countries.